BUILDING THE INDEPENDENCE OF THE CILEDUG WETAN VILLAGE COMMUNITY THROUGH THE THEMED COMMUNITY SERVICE PROGRAM - Deni Yusup Permana; Siti Aisyah Nur Hidayah; Adyatma Saputra; Mohammad Patra Aditya; Mochamad Farid; Ikrima Istiqomah Rizkha; Salwa Ardiyansyah; Ilham Purwanto; Armansyah Armansyah; Annisa Uswatun Hasanah; Naufal Ahnaf Widiyana; Salma Elvia Nabilah; Aldi Firmansya; Nur Hadi Kusumah; Wiwi Widiyawati (Ann Publisher, 2025)
Abstract: Background: Community service is one aspect of the Tri Dharma of Higher Education that contributes to social, economic, and educational development. Aim: The Thematic Community Service Program (KKN-T) aims to build the independence of the Ciledug Wetan Village community through education-based, economic, and social empowerment. Methods: This activity uses the Participation Action Research (PAR) method, which emphasizes the community's active involvement at every stage of the program, from problem identification to planning, implementation, and evaluation. Results: The activities show increased children's literacy through interactive storytelling activities, encouraging their reading interest and critical thinking. In the economic aspect, MSME actors received training in branding, digital marketing, and promotional material creation to enhance the competitiveness of local products. In addition, public awareness of environmental cleanliness has increased through education on clean and healthy living behaviors (PHBS) and the management of organic and inorganic waste. Conclusions: This program has a direct impact on the community and students through knowledge application, leadership development, and the enhancement of communication and collaboration skills. Implication: These results affirm that student involvement in community-based empowerment programs can be an effective strategy for supporting sustainable development and innovation based on local wisdom.